(untitled) (Comprehensive Journal of Science, 2025)
Acoustic comfort has been a vital aspect of the built environment, through which sustainability standards may be achieved, especially in healthcare facilities, especially hospitals. The higher noise levels, above their normal rates, may lead to several health harms, which affect both patients and healthcare providers and thus create obstacles to making the building sustainable. The research discussed the concept of sustainability in general, then touched on the study of sustainability in hospital buildings, and its environmental, social, and economic aspects. It then focused on acoustic comfort and its importance in creating a sustainable environment in hospital buildings. Acoustic comfort and permissible noise rates in hospital buildings have been identified according to regional and international standards, and the sources of internal and external noise have been identified too. The effect of higher noise rates on patients and healthcare providers has also been addressed. This paper aims to study and acknowledge the methods we may use to reduce the noise levels in hospital buildings, to reach permissible noise rates according to international standards. A case-study technique was used to identify, analyze, and measure the external noise of Ain Shams Maternity Hospital building, and then a simulation tool was employed to study and evaluate solution alternatives and treatments, making use of the acoustic properties of building materials and other design solutions to reduce the noise rates in the case-study building, and recommendations have been made do reduce noise rates to reach a sustainable healthcare building.